Comparative DFT dual gas adsorption model of ZnO and Ag/ZnO with experimental applications as gas detection at ppb level. (16th December 2021) - Kumar, Utkarsh; Huang, Shih-Ming; Deng, Zu-Yin; Yang, Cheng-Xin; Haung, Wen-Min; Wu, Chiu-Hsien
Abstract: By experimental and density functional theory calculations, the toxic gases (O3 and NO2 ) sensing capability and mechanism of ZnO NRs and Ag/ZnO NRs have been comparatively studied in this work. Ag NPs arrays were employed for the growth of ZnO NRs. The experimental results show that when ZnO NRs are grown on Ag NPs, the response and adsorption rate towards the gases change significantly. The TDOS plot shows that the HOMO-LUMO gap changes after interaction with different oxidizing gases, and the peak intensity also decreases confirming the electron are transferred from ZnO to NO2 and O3 . The response to gases decreases and the adsorption reaction rate increases in Ag/ZnO NRs, as calculated by the Eyring-Polanyi equation, which is very similar to our experimental data. We also find that the absorption coefficient is different for O3 and NO2 . Finally, experimental response and theoretical results were compared and found to be in good agreement.